The Neuroendocrine-Immune Regulation in Response to Environmental Stress in Marine Bivalves - Liu, Zhaoqun; Li, Meijia; Yi, Qilin; Wang, Lingling; Song, Linsheng (Frontiers in Physiology, 2018)
Marine bivalves, which include many species worldwide, from intertidal zones to hydrothermal vents and cold seeps, are important components of the ecosystem and biodiversity. In their living habitats, marine bivalves need to cope with a series of harsh environmental stressors, including biotic threats (bacterium, virus, and protozoan) and abiotic threats (temperature, salinity, and pollutants). In order to adapt to these surroundings, marine bivalves have evolved sophisticated stress response mechanisms, in which neuroendocrine regulation plays an important role. The nervous system and hemocyte are pillars of the neuroendocrine system. Various neurotransmitters, hormones, neuropeptides, and cytokines have been also characterized as signal messengers or effectors to regulate humoral and cellular immunity, energy metabolism, shell formation, and larval development in response to a vast array of environmental stressors. In this review substantial consideration will be devoted to outline the vital components of the neuroendocrine system identified in bivalves, as well as its modulation repertoire in response to environmental stressors, thereby illustrating the dramatic adaptation mechanisms of molluscs.